Analisis Kinerja Perusahaan Dengan Pendekatan Balanced Scorecad (Studi pada Perusahaan Daerah Air Minum Bolaang Mongondow - Makalunsenge, Irawati (Universitas Sam Ratulangi, 2018)
The purpose of this research is to analyze the organizational performance using Balanced Scorecard approach. Research was conducted in PDAM Bolaang Mongondow. This research is a descriptive study and used quantitative method. The sample was 100 customers for customer perspective and 60 employees for internal process perspective and learning and growing perspective. This research also uses financial report data to analyze the financial perspective. Analysis result indicates that, from customer perspective the result is not good. For internal process perspective, the result is categorized as averagely good. For learning and growing perspective, the obtained result is very good, while from the financial perspective, Kantor PDAM Bolaang Mongondow categorized as not economical, not efficient and not effectiveKeywords: Balanced Scorecard, Customer Perspective, Internal Process Perspective, Learning and Growing Perspective, Financial Perspective